Pengaruh Kapabilitas Relasi Terhadap Penciptaan Nilai dan Kinerja Pemasaran Dengan Kapabilitas Pemasaran Dinamis Sebagai Variabel Moderasi - Hutagalung, Syopwan Alrasid; Aditi, Bunga; Fahlevi, Alvin (Yayasan Cita Cendekiawan Al Khwarizmi, 2022)
The results in this study indicate that the variables of relational capabilities and have a significant influence on value creation and market performance,. For the dynamic market capabilities variable which acts as a moderating variable, in this study the variable dynamic market capabilities is not able to moderate positively between the variables of relational capabilities with value creation and market performance This study aims to determine relation capabilities, on interest in value creation and market performance with dynamic market capabilities as a moderating variable (research study on owner brand clothing in Medan city). The research design used moderated multiple linear regression analysis. as an analytical tool to find out how the influence between the independent and dependent variables is moderated by the moderating variable. This study uses an associative research type with a quantitative approach. The population and sample in this study, namely for the population based on owner brand clothing in Medan city with a sample of 101owner brand clothing in medan city.